2022
DOI: 10.3390/ma15197035
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Failure Behavior of Brittle Heterogeneous Rock under Uniaxial Compression Test

Abstract: Rocks have formed heterogeneous characteristics after experiencing complex natural geological processes. Studying the heterogeneity of rocks is significant for rock mechanics. In this study, a linear parallel bond model with Weibull distribution in two-dimensional particle flow code (PFC2D) is adopted to study the mechanical characteristics and brittle failure mode of granite rock specimens with different heterogeneity. Firstly, we selected several combinations of key micro-parameters of the parallel bond mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…With more dry–wet cycles, the analysis steps corresponding to crack initiation and penetration for the sandstone specimen are advanced, and the quantity of analysis steps from crack initiation to penetration is reduced, indirectly indicating the continuous accumulation of internal damage in the sandstone specimen with more dry–wet cycles. The findings were in agreement with the results of Liu et al 45 and Chen et al 46 on sandstone research. A linear regression of the number of analysis steps and the number of cracks in sandstone with different numbers of wet and dry cycles and the number of cracks produced and the crack penetration in sandstone with different numbers of wet and dry cycles showed that the fitting coefficients were 0.942 and 0.898, respectively, which further showed that with the increase of the number of cycles, the compressive strength of sandstone gradually decreased, the extension of the cracks intensified, and sandstone was more likely to tend to damage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With more dry–wet cycles, the analysis steps corresponding to crack initiation and penetration for the sandstone specimen are advanced, and the quantity of analysis steps from crack initiation to penetration is reduced, indirectly indicating the continuous accumulation of internal damage in the sandstone specimen with more dry–wet cycles. The findings were in agreement with the results of Liu et al 45 and Chen et al 46 on sandstone research. A linear regression of the number of analysis steps and the number of cracks in sandstone with different numbers of wet and dry cycles and the number of cracks produced and the crack penetration in sandstone with different numbers of wet and dry cycles showed that the fitting coefficients were 0.942 and 0.898, respectively, which further showed that with the increase of the number of cycles, the compressive strength of sandstone gradually decreased, the extension of the cracks intensified, and sandstone was more likely to tend to damage.…”
Section: Discussionsupporting
confidence: 93%
“…The analysis of Fig. 11 a shows that the number of cracks increases with the higher number of wet and dry cycles, which is consistent with the findings of Liu et al 44 and Liu et al 45 in rock studies. This may be due to the effects of factors such as physical and chemical interactions between the water and the rock, which result in a one-time increase in the penetration of the water molecules and a decrease in the load-bearing capacity of the sandstone specimens.…”
Section: Discussionsupporting
confidence: 89%
“…To establish the parallel bond model, we need to calibrate its mesoscopic parameters. The mesoscopic parameters include the shape, size, distribution, density, stiffness, etc., of the particles, which directly affect the macroscopic mechanical properties of the model [27,28]. Based on the macroscopic mechanical parameters of the uniaxial compression test, we used the inverse analysis method by adjusting the values of the mesoscopic parameters, to make the stress-strain curve of the model as close as possible to the test curve [29].…”
Section: Numerical Model Establishmentmentioning
confidence: 99%
“…The wear of the discharge baffle is the process of changing from a continuous medium to a discrete medium. The discrete element analysis method is used to discrete the discharge baffle material into rigid spheres and establish a three-dimensional linkage model to study the dynamic process of changing the surface material of the discharge baffle from a continuous medium to a discrete medium [6]. The material of the discharge baffle is mostly a high-chromium manganese wear-resistant material, and its organization is a face-centered cubic structure shown in figure 1, including four 1/2 sphere units and eight 1/8 sphere units, each of which is surrounded by 12 other sphere units.…”
Section: Discharge Bafflementioning
confidence: 99%